Outsourcing procesów biznesowych - Sobińska, Małgorzata (Business Process Outsourcing, 2009)
The aim of the article is to show the concept of Business Process Outsourcing (BPO). The idea of different models of the outsourcing relationship is defined. Then the author focuses on the profile of Business Process Outsourcing as a model becoming more and more popular, especially among large organizations. The author points at the key motives of the BPO decisions, risks and rules of the outsourcing relationship management. Stages and elements of services centers forming projects are also presented. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 52, s. 199-206